Plume overriding triggers shallow subduction and orogeny in the southern Central Andes - Gianni, Guido Martin (2017)
Plate tectonic theory implies that mantle plumes may be eventually overridden by lithosphere during continental drift. These events have particular tectonomagmatic consequences for active margins and hence related orogenic processes. Since the first documentation of plume overriding and the definition of the plume-modified orogeny concept, only few examples have been recognized in the geologic record. In this study, we analyze the Neogene tectonic evolution of the Southern Central Andes between 35° and 38°S and its potential relation to the subduction of the Payenia plume as a recent analogue of this process. Through a series of tectonic reconstructions we show that progressive Payenia plume overriding correlates with Neogene arc-front migrations linked to slab shallowing, fold belt reactivation in the Main Cordillera and intraplate contraction in the San Rafael block. Additionally, Nazca slab tear determined from tomographic analyses and subsequent diachronous steepening of the subducted plate may also be an aftermath of plume subduction as often described in the final stages of plume-modified orogeny. Finally, we propose a modern analogue for processes previously described, dating back to the Mesoproterozoic, which provides further insights into these complex settings.